2017
DOI: 10.1016/j.addbeh.2016.08.025
|View full text |Cite
|
Sign up to set email alerts
|

Perceived risk of heroin use among nonmedical prescription opioid users

Abstract: Aims The prevalence of heroin use among nonmedical prescription opioid (NMPO) users has increased in recent years. Identifying characteristics associated with heroin use in this population can help inform efforts to prevent heroin initiation and maintenance. The aim of this study was to evaluate differences in perceived risk of heroin among NMPO users with and without histories of heroin use, and to examine temporal trends in perceived risk of heroin among this population. Methods Data are from the 2002–2013… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 44 publications
(64 reference statements)
0
11
0
Order By: Relevance
“…61 Major depressive disorder was assoc iated w ith SUDs, particularly drug disorders, as found previously for cannabis, 40,62 nonmedical prescription opioids, 5,57,63 and drug use disorders. 41 With increasingly positive attitudes toward substance use [64][65][66] and increasing rates of adult SUDs and associated problems, 24,41,42,67-69 MDD comorbidity with SUDs remains a substantial public health 24,70 and economic 16 burden. Evidence suggests that efforts to selfmanage depression with cannabis are increasing [71][72][73][74][75] (also Aaron L. Sarvet, MPH, written communication, January 2, 2018) despite lack of evidence that cannabinoids are effective for this purpose 76,77 ; prospectively, cannabis worsens the course of depressive disorders.…”
Section: Discussionmentioning
confidence: 99%
“…61 Major depressive disorder was assoc iated w ith SUDs, particularly drug disorders, as found previously for cannabis, 40,62 nonmedical prescription opioids, 5,57,63 and drug use disorders. 41 With increasingly positive attitudes toward substance use [64][65][66] and increasing rates of adult SUDs and associated problems, 24,41,42,67-69 MDD comorbidity with SUDs remains a substantial public health 24,70 and economic 16 burden. Evidence suggests that efforts to selfmanage depression with cannabis are increasing [71][72][73][74][75] (also Aaron L. Sarvet, MPH, written communication, January 2, 2018) despite lack of evidence that cannabinoids are effective for this purpose 76,77 ; prospectively, cannabis worsens the course of depressive disorders.…”
Section: Discussionmentioning
confidence: 99%
“…The responses were on a 4-point scale, labelled as "great risk," "moderate risk," "slight risk," and "no risk." We dichotomized responses into "great risk" and "less than great risk," similarly to other studies of perceived risk using NSDUH (Lipari et al, 2017;Pacek et al, 2015;Votaw et al, 2017).…”
Section: Outcome Variablesmentioning
confidence: 99%
“…Cross-sectional studies have shown that individuals who use a particular substance may perceive that behavior as lower risk, compared to individuals who do not (Chomynova et al, 2009;Lipari et al, 2017;Pacek et al, 2015). One such study of people who used prescription pain relievers showed that those who had previously used heroin were much less likely to feel heroin use as being very risky, compared to those who had not used heroin (Votaw et al, 2017). Longitudinal studies have also explored this link, showing that the perceived harmfulness of a substance may be inversely associated with subsequent use.…”
Section: Introductionmentioning
confidence: 99%
“…Dramatic increases in overdoses from prescription opioids and the transition to heroin use among nonmedical users of prescription opioids has certainly captured the attention of community leaders across the nation. In this issue, Votaw et al (2016) analyzed multiple years of data from the National Survey of Drug Use and Health (NSDUH) and showed a significant association between low perceived risk of regular heroin use and using heroin among nonmedical prescription opioid users. In an analysis of injection drug users, Al-Tayyib et al (2016) found that 32% reported being hooked on prescription opioids prior to initiating injection drug use.…”
Section: Introductionmentioning
confidence: 99%